Studying the cellular origin of HSCs in the zebrafish embryo and the role of Gfi1 transcription factors in their formation - Jalali, Maryam (2017)
In vertebrates, haematopoietic stem cells (HSCs) maintain the blood system throughout life. HSCs are believed to arise during embryogenesis from haemogenic endothelial cells (HECs) that undergo an endothelial-to-haematopoietic transition (EHT). Here, in order to trace the progeny of the embryonic ECs in zebrafish, an inducible CreERT2-LoxP system was used. Following short-term induction of the Cre recombinase during early embryonic stages, Cre reporter gene expression was observed in early larval haematopoietic cells (HCs). At adult stages, PCR revealed the presence of the recombined Cre reporter gene in HCs, demonstrating that adult HCs had originated from embryonic ECs. In zebrafish, HECs of the ventral wall of the dorsal aorta (vDA) are thought to form HCs by basal epithelial-to-mesenchymal transition (bEMT), a process that depends on the transcription factor Runx1. Here, making use of the recently identified gfi1aaqmc551Gt line, confocal microscopy showed that qmc551: GFP+ cells were HECs. While most GFP+ cells underwent bEMT, some displayed a novel type of apical departure. In runx1morphants, bEMT was abrogated and most GFP+ HECs remained in the vDA. Apical departure, however, was still observed in the absence of Runx1, suggesting a fundamental difference in the underlying mechanism.While gfi1aa expression was lost in vDA HECs of qmc551 homozygous embryos, EHT of GFP+ HECs was completely unaffected. Up regulation of its paralogue Gfi1ab suggested functional redundancy. To study this redundancy, the CRISPR/Cas9 system was used to mutate the gfi1ab gene. Here, the mutant gfi1ab alleles qmc552 and qmc553 were identified. Both alleles, as well as a third allele sh320 that was generated by a collaborator, encode truncated, most likely non-functional proteins. Initial data on gfi1aaand gfi1ab double mutant embryos showed a defect in definitive haematopoiesis. Whether HECs were affected and blocked in their ability to undergo EHT remains to be determined.